Sistem Sewa Lahan Pertanian Masyarakat Pedesaan dalam Perspektif Ekonomi - Utomo, Selamet Joko; Wulandari, Dwi (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
This study aims to analyze the system of agricultural land leases carried out by landowners in rural Ngronggot Nganjuk District with qualitative research methods. The results of this study found that the land leasing system is called the Ngronggot Village community of Nganjuk Regency as the "Annual Adol". In the "Annual Adol" system, there are three stages of agreement found, namely: Pre agreement, Agreement, and after agreement. In an economic perspective the phenomenon of agricultural land rent is carried out by landowners against the backdrop of economic rationality which provides a higher opportunity cost when deciding to lease land compared to working on agricultural land itself mainly related to the risk of crop failure and the amount of harvest produced is lower than the cost his farming business. Whereas for land tenants the economic rationality underlying is that the greater the mastery of the cultivated agricultural land, the greater economic benefits received by the land tenant.